A new approach to assessing the efficacy of anthelmintic agents in vitro - E. A. Perina; E. E. Buyko; I. P. Kaminskiy; D. S. Sobakin; A. A. Ufandeev; O. A. Kaidash; V. V. Ivanov; E. V. Udut (Бюллетень сибирской медицины)
Aim. To develop a new method to determine the viability of Opisthorchis felineus in vitro using the MTS reagent and to evaluate its applicability for analyzing the efficacy of anthelmintic agents in the treatment of opisthorchiasis.Materials and methods. Golden hamsters were used to create a model of O. felineus infection. The animals were infected with metacercariae obtained from fish of the Cyprinidae family. Three months after infection, adult parasites were extracted from the hepatobiliary system. Their viability was assessed using the motility scale and a new method based on the modified MTS test protocol. To account for differences between the size and number of adult parasite cells, the results were normalized with respect to protein content. To evaluate the feasibility of the new approach in the study of pharmacological activity against opisthorchiasis, the viability of adult parasites in the presence of praziquantel was tested.Results. During incubation of adult flukes in a medium with the addition of the MTS reagent, colored watersoluble formazan was accumulated. Thermal inactivation of parasites significantly decreased the production of this compound. Since the studied adult parasites differed in size and number of cells, the obtained data on their viability were normalized to protein content. The results correlated with the data on parasite viability obtained by the traditional method using the motility scale. Evaluation of praziquantel efficacy at different concentrations using two independent methods (the MTS test and the motility scale) showed that the results of the MTS test were consistent with literature data and comparable with the results obtained using the motility scale.Conclusion. A new method for in vitro evaluation of anti-opisthorchiasis activity of drugs was developed. It is based on the assessment of water-soluble formazan production by adult O. felineus flukes in the culture medium using the MTS reagent for screening anti-opisthorchiasis activity of new anthelmintic drugs.